Comparison of Government Administration Policies in Indonesia: Case of Major Cities VS Remote Areas - Natsir Mallawi; Nurasia Natsir (Proceeding of the International Conference on Social Sciences and Humanities Innovation, 2024)
This research investigates the comparison of government administration policies between major cities and remote areas in Indonesia, focusing on how these differences impact public service delivery and administrative effectiveness. Utilizing a comparative analysis method, the study examines various dimensions such as policy implementation, available resources, and the resulting public service outcomes in both contexts. The findings reveal a significant disparity in the quality of administration between urban and rural regions. Major cities benefit from better infrastructure, higher budget allocations, and more skilled personnel, which contribute to more effective service delivery. In contrast, remote areas face numerous challenges, including limited access to resources, inadequate infrastructure, and a lack of trained personnel, which hinder their ability to implement policies effectively. Moreover, the research highlights that the differences in administrative capacities lead to varying levels of public satisfaction and trust in government institutions. Citizens in major cities generally report higher satisfaction with public services compared to those in remote areas, where frustrations are often linked to delays and inefficiencies. This study emphasizes the urgent need for more inclusive and equitable policies aimed at enhancing government administration in remote areas. By addressing the systemic challenges faced by these regions, policymakers can work towards reducing the administrative gap and ensuring that all citizens, regardless of their geographical location, receive quality public services.